TECHNIQUE OF SYNTHESIS OF THE ADAPTIVE PERSPECTIVE NETWORK OF THE BROADBAND RADIO ACCESS - A. Yu. Zalizko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The technique of synthesis of an adaptive network of a broadband radio access (SBWA), consisting in carrying out of optimization of mathematical model of the received communication system taking into account its adaptation to influence of external negative factors is considered. Structurally-parametrical adaptation in which basis the structural component lays is thus used.